The Effect of the Adaptive Mentality “MANTAP” Program on Resilience and Stress Levels in Nursing Students: A Quasi-Experimental Study - Amaliyah, Eli; Sulastri, Tuti; Puspasari, Ike (Media Publikasi Cendekia Indonesia, 2025)
The